Biomechanical effects of saddle height changes in leisure cycling with unilateral transtibial prostheses: A simulated study - Heloisa Seratiuk Flores; Yeoh Wen Liang; Ping Yeah Loh; Kosuke Morinaga; Satoshi Muraki (PLoS ONE, 2025)
Cycling is a beneficial physical activity for rehabilitating individuals with lower-limb amputations and serves as a feasible leisure sport. However, the optimal bicycle configuration for cycling with a unilateral transtibial prosthesis at leisure levels has not been investigated. For saddle height at professional cycling levels, existing literature suggests utilizing the same configuration as that used by intact cyclists, where the knee reaches 25–35° at maximum extension. However, leisure cyclists tend to select lower saddle heights, and cycling with a unilateral transtibial prosthesis infers altered biomechanics during cycling practice. This study aimed to investigate the effects of cycling at different saddle heights with a simulated unilateral prosthesis. Ten able-bodied participants wore orthoses to simulate prosthetic conditions. The experimental task was performed on an ergometer at 40 W resistance, 60 rpm to simulate leisure cycling. Standard saddle height was defined as maximum knee extension of 45°. This height was used as the control condition and its trials were performed without orthoses. The variable heights were set as height percentage variations (-7%, -3.5%, 0, +3.5%, and +7%). Muscle activity, joint movement, force application to the pedals, perceived exertion, and comfort were evaluated. The -3.5% and -7% saddle heights resulted in joint movement and muscle activity levels closer to those in the control conditions, which also showed improved power symmetry between the affected and non-affected legs. In addition, the -3.5% height increased comfort level in participants. In conclusion, selecting lower saddle heights may be beneficial for unilateral transtibial amputees during leisure cycling. The optimal saddle height for this population may maintain maximum knee extension within the 37–45° range, dynamically measured on the affected side.